2023
DOI: 10.1007/s12225-023-10124-w
|View full text |Cite
|
Sign up to set email alerts
|

Afrothismiaceae (Dioscoreales), a new fully mycoheterotrophic family endemic to tropical Africa

Martin Cheek,
Marybel Soto Gomez,
Sean W. Graham
et al.

Abstract: SummaryAfrothismia is a genus of non-photosynthetic mycoheterotrophs from the forests of continental tropical Africa. Multiple phylogenetic inferences using molecular data recover the genus as sister to a clade comprising mycoheterotrophic Thismiaceae and the photosynthetic family Taccaceae, contrary to earlier placements of Afrothismia and Thismiaceae within Burmanniaceae. Morphological support for separating Afrothismia from the rest of Thismiaceae has depended on the zygomorphic flowers of Afrothismia (alth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…(Afrothismiaceae, Cheek & Williams 1999; Cheek et al . 2019; Cheek et al . 2023d) and at least two species of the African genus Inversodicraea (Cheek et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Afrothismiaceae, Cheek & Williams 1999; Cheek et al . 2019; Cheek et al . 2023d) and at least two species of the African genus Inversodicraea (Cheek et al .…”
Section: Discussionmentioning
confidence: 99%
“…(Thismiaceae,Cheek et al 2018b) and Afrothisia pachyantha Schltr. (Afrothismiaceae,Cheek & Williams 1999;Cheek et al 2023d) and at least two species of the African genus Inversodicraea(Cheek et al 2017), are well known examples, recently joined by species such as Vepris bali Cheek (Rutaceae,Cheek et al 2018c), Vepris montisbambutensis Onana(Onana & Chevillotte 2015) and Ardisia schlechteri Gilg (Murphy…”
mentioning
confidence: 99%
“…(Afrothismiaceae, Cheek & Williams 1999; Cheek et al . 2019; Cheek et al . 2024) are well known examples, recently joined by species such as Vepris bali Cheek (Rutaceae, Cheek et al .…”
Section: Discussionmentioning
confidence: 99%
“…Among mycoheterotrophic plants, Orchidaceae and Ericaceae plants have been found to associate with Basidiomycota and Ascomycota, whereas other plant families associate with Glomeromycotina (i.e., AM fungi). There are at least 330 species of mycoheterotrophic AM plants in nine angiosperm families (Merckx et al 2013b ; Cheek et al 2024 ; Imhof 2024 ), and Paris -type AM have been observed in all plants examined (Imhof et al 2013 ). Recently, Giesemann et al ( 2021 ) suggested that partial mycoheterotrophy (mixotrophy), obtaining carbon compounds via both photosynthesis and mycoheterotrophy, may be common among chlorophyllous plants with Paris -type AM based on the enrichment of 13 C and 15 N. Along with the observation that understory plants typically develop Paris -type AM (Brundrett and Kendrick 1990 ; Yamato and Iwasaki 2002 ), it has been suggested that Paris -type AM may be a prerequisite for the evolution of mycoheterotrophy (Imhof 1999 ; Giesemann et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%